'Give the Money Where it's Due': The Impact of Knowledge-Sharing via Social Media on the Reproduction of the Academic Labourer. (4th March 2022) - Arboledas-Lérida, Luis
ABSTRACT: This paper addresses the impact that the ever-growing involvement of scientists in knowledge-sharing practices by means of social media might have on the material conditions under which academic labour-power reproduces itself. Science communication is advocated for on the basis of its supposedly altruistic character, so scientists are prevented from expecting any form of remuneration ensuing from it. However, as our Marxian-informed analysis of the determinations of the value of the commodity labour-power will elucidate, this novel duty involves the exertion of an additional quantity of work by academics, owing either to the relative complexation of the productive attributes requisite to use social media efficiently, or, particularly, to the accelerated pace at which scientists' working capacity becomes productively consumed, both in absolute (extension of working hours) and in relative (work intensification) terms. It will be demonstrated that, as science communication via social media brings about an increase in the value of scientific labour power, wages must be raised so as to preserve science labourers in their normal condition. The article will further throw into relief that the political action of scientists themselves stands as the more general mediation for this innermost necessity of the capitalistic relationship of production to assert itself.